Smallholder Farmers’ Knowledge and Attitudes Toward Adoption of Exotic Bamboo in Southwest Ethiopia - Wakweya, Rusha Begna; Abdeta, Diriba; Zerfu, Haile; Negassa, Alemayehu; Lemineh, Beliyu (CV. Literasi Indonesia, 2024)
Bamboo is a fast-growing forest resource that offers significant economic potential and can contribute to sustainable development. Farmers' knowledge and attitudes about exotic bamboo influence the successful adoption and effective utilization of the technology. Enhancing farmers' knowledge and positive attitudes towards exotic bamboo can create economic opportunities and ensure environmental sustainability. However, empirical evidence on farmers' knowledge and attitudes towards exotic bamboo practices is limited. This study aims to assess farmers' knowledge and attitudes towards the adoption of exotic bamboo species through a combined survey and field demonstration in southwest Ethiopia over the past three years. The field demonstration is supported by continuous training and follow-up. A multi-stage sampling technique was used to select 30 respondents. The collected data was analyzed using descriptive statistics and correlation analysis. The results indicate that participating respondents had a low level of knowledge and positive attitudes towards adopting exotic bamboo before the implementation of the program. The outcomes of a three-year field demonstration program show the effectiveness of providing smallholder farmers with information and knowledge about the adoption and management of exotic bamboo technology. Almost all respondents recognize the importance of implementing exotic bamboo to narrow the demand and supply gap of wood and forest management. Moreover, the results reveal a positive correlation between farmers' knowledge and their willingness to adopt exotic bamboo technology. Therefore, the finding suggests the provision of capacity-building training and extension services for farmers to increase their knowledge and positive attitudes toward the adoption of exotic bamboo management practices.